Fibromyalgia Management: Rehabilitation Approaches - Murat Zinnuroğlu (Archives of Rheumatology, 2007)
Fibromyalgia is characterized by long-lasting, widespread pain and generalized tenderness, usually accompanied by fatigue. There are fewer studies on the efficacy of non-pharmacologic rehabilitative treatment approaches compared with pharmacologic treatment choices. In this review, particularly randomized controlled studies on rehabilitative techniques which are indispensable for fibromyalgia treatment have been overviewed. The efficacy of aerobic exercises, patient education, self management techniques and cognitive-behavioral therapies is more when compared with other treatment modalities. Main beneficial exercise types are whole body aerobic exercises, cycling, dance, walking, pool exercises, stretching and strengthening exercises. The most important member of a successful management team is a well-educated patient who has the ability to maintain the treatment program and make appropriate arrangements according to fluctuations in symptoms. The most efficient education programs emphasize self-efficacy and the patients who get beter results are those having more self-efficacy thus adapting more easily. Consequently, we must consider that fibromyalgia syndrome is characterized by multisystem symptoms and so multidisciplinary (multimodal) therapies should be preferred as it has been shown with many previous studies. (Rheumatism 2007; 22: 104-9)